2013
DOI: 10.1175/jcli-d-12-00267.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Forcing of the Winter Air–Sea Heat Fluxes over the Northern Red Sea

Abstract: The influence of the atmospheric circulation on the winter air-sea heat fluxes over the northern Red Sea is investigated during the period 1985-2011. The analysis based on daily heat flux values reveals that most of the net surface heat exchange variability depends on the behavior of the turbulent components of the surface flux (the sum of the latent and sensible heat). The large-scale composite sea level pressure (SLP) maps corresponding to turbulent flux minima and maxima show distinct atmospheric circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 37 publications
1
86
1
Order By: Relevance
“…These depressions originally develop in the North Atlantic Ocean and the central Mediterranean and then move to the east, enhanced by the deepening upper level trough and the lee-low effect of the Cyprus mountains (Almazroui, 2006). Papadopoulos et al (2013) indicated that the low pressure originating over both the east Mediterranean and equatorial Africa shifts during winter to be placed over the Red Sea. According to Cullen et al (2002) and Kahya (2011), the winter cyclones over the Middle East region are significantly impacted not only by changes in the Atlantic westerly heat/moisture transport controlled by the NAO, but also by changes in sea surface temperatures (SSTs) between the Atlantic and the Mediterranean.…”
Section: Reanalysis Derived Patterns In Weather Typesmentioning
confidence: 99%
“…These depressions originally develop in the North Atlantic Ocean and the central Mediterranean and then move to the east, enhanced by the deepening upper level trough and the lee-low effect of the Cyprus mountains (Almazroui, 2006). Papadopoulos et al (2013) indicated that the low pressure originating over both the east Mediterranean and equatorial Africa shifts during winter to be placed over the Red Sea. According to Cullen et al (2002) and Kahya (2011), the winter cyclones over the Middle East region are significantly impacted not only by changes in the Atlantic westerly heat/moisture transport controlled by the NAO, but also by changes in sea surface temperatures (SSTs) between the Atlantic and the Mediterranean.…”
Section: Reanalysis Derived Patterns In Weather Typesmentioning
confidence: 99%
“…1a (Papadopoulos et al 2013;Abualnaja et al 2015) as well as with other modern-era reanalyses, such as MERRA (Abualnaja et al 2015). The climatological maximum of annual precipitation (Fig.…”
Section: B Methodsmentioning
confidence: 75%
“…The Red Sea is a unique basin characterized by extremely high evaporation, which amounts to 1.6-1.9 m yr 21 for the whole sea (Tragou et al 1999) and may increase to more than 3 m yr 21 in the northern part (e.g., Papadopoulos et al 2013). Upon rising into the atmosphere, this moisture participates in the regional hydrological cycle, influencing water content and precipitation over the adjacent continents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations